2018
DOI: 10.1155/2018/8363295
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mechanism of Danshen against Myelofibrosis by Network Pharmacology and Molecular Docking

Abstract: Danshen (Salvia miltiorrhiza Bunge), a natural powerful drug for various conditions treatment, has traditionally been used in Asian countries for centuries as anticancer agent, anti-inflammatory agent, and antioxidant. More recently, it is explored in combination with other herbs for skeletal diseases therapy; bone-targeting compounds with pharmacological activities have been isolated from various sources of traditional Chinese medicine (TCM), including Danshen. In this case, some evidence supports that Danshe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Molecular docking was the widely use technology for calculating protein-ligand interactions [35]. And the results also showed that Quercetin could docked well with MAPK3, IL-6 and TP53.…”
Section: Discussionmentioning
confidence: 96%
“…Molecular docking was the widely use technology for calculating protein-ligand interactions [35]. And the results also showed that Quercetin could docked well with MAPK3, IL-6 and TP53.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, in ammation factors and apoptosis factors (MAPK3, IL-6 and TP53) were signi cantly downregulated by Quercetin. Given that in ammation and apoptosis were closely related with pancreatitis, they were likely to be the molecules regulated by Xiaochaihu Decoction in the treatment of pancreatitis.Molecular docking was the widely use technology for calculating protein-ligand interactions [36]. And the results also showed that Quercetin could docked well with MAPK3, IL-6 and TP53.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Yeung et al [22] analyzed 100 most cited papers in ethnopharmacology and highlighted the importance of traditional medicine in medicine and food science. Pathway and network analysis and protein-protein interactions are common methods for NP [68, 23]. Oral bioavailability [24] is an essential parameter for drug absorption and utilization; therefore, NP studies commonly use this alone or in combination with other parameters, including drug likeness, Caco-2 permeability, and drug half-life, as filters to select compounds from herbs [6, 7, 25].…”
Section: Discussionmentioning
confidence: 99%